Pengaruh Pengetahuan Keuangan Terhadap Perilaku Keuangan Dengan Gaya Hidup Sebagai Variabel Mediasi Pada Mahasiswa Program Studi S1 Pendidikan Akuntansi Fakultas Ekonomika Dan Bisnis Universitas Negeri Surabaya - Yasin, Ilmatul Fitriana; Wahjudi, Eko (Pusat Riset dan Inovasi Nasional, 2026)
One of the most discussed issues today is financial behavior. This is because people who already have sufficient income often experience financial problems due to irresponsible financial behavior. This is common among Generation Z, especially students, who are influenced by a hedonistic lifestyle. Financial knowledge plays a crucial role in supporting healthy financial behavior. The higher a person's financial knowledge, the better they will be at managing their finances, including making investment decisions, saving, and avoiding excessive debt. This type of research is quantitative research. The sampling technique used simple random sampling with 210 respondents. The research instruments used were questions from the OECD and a questionnaire. Data were analyzed using multiple linear regression analysis using SPSS 25 software. The results of this study indicate that financial knowledge (X) influences financial behavior (Y) by 2.103, supported by a significance level of 0.037 <0.05. Financial knowledge (X) influences lifestyle (Z) by 4.291, supported by a significance level of 0.003 <0.05. Lifestyle (Z) influences financial behavior (Y) by 5.836, supported by a significance level of 0.000 < 0.05. Financial knowledge (X) influences financial behavior (Y) through lifestyle (Z) as mediated by a Sobel test result of 3.457.